A Review of Post-operative Pain Management of Hallux Valgus Procedures - Biglari , Farsad; Jafari Kafiabadi , Meisam; Sabbaghzadeh, Amir (Archives of Men's Health, 2023)
Background: The management of hallux valgus is important in orthopedic surgery. The purpose of the current study was to look into the techniques for reducing pain after surgery for hallux valgus. Method: The results of this study were obtained by reviewing English-language papers about foot and ankle surgery that were published in the PubMed and Scopus databases between 1991 and 2021. Ultimately 41 articles were retrieved. Results: Based on the results of this study, systemic steroids and opioids, when used without paracetamol, non-steroidal anti-inflammatories, and cyclo-oxygenase inhibitors II, can be used properly to provide analgesia during hallux valgus surgery. Conclusion: Postoperative analgesics and sciatic nerve blocks in conjunction with other techniques are used to manage the pain after this procedure.